2010
DOI: 10.1016/j.virol.2010.02.016
|View full text |Cite
|
Sign up to set email alerts
|

A human cytomegalovirus deleted of internal repeats replicates with near wild type efficiency but fails to undergo genome isomerization

Abstract: The class E genome of human cytomegalovirus (HCMV) contains long and short segments that invert due to recombination between flanking inverted repeats, causing the genome to isomerize into four distinct isomers. To determine if isomerization is important for HCMV replication, one copy of each repeat was deleted. The resulting virus replicated in cultured human fibroblasts with only a slight growth impairment. Restriction and Southern analyses confirmed that its genome is locked in the prototypic arrangement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Virus HB15-t178b was derived from bacterial artificial chromosome (BAC) clone HB15Tn7Δk [13], which contains the CMV strain AD169 genome [14], by transposition of a green fluorescent protein (GFP) reporter cassette into the att Tn7 site, as described [15]. Virus HB15-t178b retains a UL131 frame shift mutation intrinsic to strain AD169.…”
Section: Methodsmentioning
confidence: 99%
“…Virus HB15-t178b was derived from bacterial artificial chromosome (BAC) clone HB15Tn7Δk [13], which contains the CMV strain AD169 genome [14], by transposition of a green fluorescent protein (GFP) reporter cassette into the att Tn7 site, as described [15]. Virus HB15-t178b retains a UL131 frame shift mutation intrinsic to strain AD169.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant mutants of HSV-1 that are not able to undergo homologous recombination due to the deletion of part or all of the inverted repeats at the junction between the L and S fragments (a=b=/a=c=) showed lower efficiency of replication in vitro than the corresponding wild-type virus and an absence of acute infection in vivo (27,28,41,46). These observations suggest that either the doubled rate of synthesis of proteins encoded by the b=a=/a=c= sequences and/or the ability to undergo homologous recombination is required for efficient in vivo infection.…”
mentioning
confidence: 99%
“…To our knowledge, this paper is the first report that describes a mutant herpesvirus of group D that lacks the entire internal inverted repeat and has as a consequence a genome that can only exist as a single isomer. Previous reports on the organization of the genome of herpes simplex virus 1 mutants by Roizman and coworkers (Jenkins and Roizman, 1986; Poffenberger and Roizman, 1985; Poffenberger et al, 1983) and a recent report (Sauer et al, 2010) describing a genomic mutant of human cytomegalovirus showed that these group E genomes that normally are composed as equal amounts of four isomers can exist in a single isomeric arrangement that fails to invert. These mutant forms of the genomes of HSV-1 and CMV and now EHV-1 that fail to undergo isomerization are capable of replication in cell culture with an efficiency similar to that of wild type virus.…”
Section: Discussionmentioning
confidence: 97%